Effect of Conversion Point Moisture Content on Quality of Dried Macrobrachium rosenbergii Meat during Vacuum Freezing Combined with Instant Controlled Pressure Drop Drying - Xiaoning CHENG; Zhuo ZHANG; Ya ZHAO; Qilong SHI; Ruichang GAO; Xiangdong JU (Shipin gongye ke-ji)
Aiming at solving the problem of high energy consumption in vacuum freeze drying (VFD), instant controlled pressure drop (DIC) was used due to its puffing capacity during drying in combination with VFD. The effect of different conversion point moisture content (60%, 50%, 40% and 30%) on the drying kinetics, microstructure and quality characteristics of dried Macrobrachium rosenbergii were investigated. The Macrobrachium rosenbergii meat with VFD alone was also carried out for comparison. The result showed that compared with VFD alone, the drying time was significantly shortened and drying efficiency improved. Compared to the products obtained from VFD alone, VFD-DIC produced a severely damaged structure, significant volume shrinkage and quality degradation when the conversion point moisture content was 60%. With the decrease of the conversion point moisture content, the quality of dried Macrobrachium rosenbergii meat gradually approached to products obtained with VFD alone. When the conversion point moisture content was 30%, the crude protein content, shrinkage rate and texture properties of Macrobrachium rosenbergii meat were not significantly different from those obtained from the VFD alone (P>0.05). Correlation analysis showed that transverse relaxation time was significantly correlated with the quality characteristics (P<0.05). Hierarchical cluster analysis showed that the quality of shrimp meat with the conversion point moisture content of 30% was in the same cluster as the CK. In conclusion, when the conversion point moisture content was 30%, the quality of VFD-DIC Macrobrachium rosenbergii meat was close to that of the VFD alone, but the drying efficiency was significantly enhanced. This study can provide theoretical basis and practical reference for high quality and efficient drying of Macrobrachium rosenbergii meat, especially VFD.